Generalized order statistics from Kumaraswamy distribution and its characterization - Kumar, Devendra (Tamsui Oxford Journal of Mathematical Sciences)
We give explicit expressions and some recurrence relations for single and product moments of generalized order statistics from Kumaraswamy distribution. The results include as particular cases the above relations for moments of reversed order statistics and records. Further, using a recurrence relation for single moments we obtain characterization of Kumaraswamy distribution.